Hydrokuinon Analytic On Night Cream From Beauty Clinic At Jl Margonda Depok Analyzed Using High Performance Liquid Chromatography Method (HPLC) - Ai Emalia Sukmawati; Evaliani Surachman; Dewi Purnamasari (Politeknik Kesehatan Kemenkes Jakarta II, 2017)
The research of the existence of Hydroquinone content in the night cream product from all beauty clinic at JL. Margonda Raya-Depok. Hydroquinone is a skin bleaching, it’s a derivative of benzene and it’s banned for purposes of usage on the skin because it can cause permanent damage. The purpose of this study was to perform qualitative and quantitative analysis of a hydroquinone content in a night cream from all beauty clinics at Jl. Margonda Raya Depok. 4 (four) product for test materials obtained randomly from 10 existing clinics, and analyzed using high-performance liquid chromatography. With reference to the requirements set forth by the National Food and Drug Agency through Head of National Food and Drug Agency Regulation No: HK. 03.1.23.08.11.07517 in 2011 about technical requirements for Cosmetic Ingredients, Hydroquinone is not allowed occur on the product for the skin or hair so the cream products A, B and D declared ineligible whereas C cream product is qualified.